2012
DOI: 10.1007/s00192-012-1703-5
|View full text |Cite
|
Sign up to set email alerts
|

Increased microRNA-221/222 and decreased estrogen receptor α in the cervical portion of the uterosacral ligaments from women with pelvic organ prolapse

Abstract: Elevated miR-221/222 expression levels are associated with, and may be responsible for, reduced ERα expression in the cervical portion of uterosacral ligaments of patients with POP. MiR-221/222 may serve as potential therapeutic targets for POP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…While this work was in progress, Shi et al . also found that miR-222 expression is increased in the USLs of women with POP compared to normal counterparts and that there is an inverse correlation between ERα protein and miR-222 expression 33 . In conclusion, based on Shi et al .…”
Section: Discussionmentioning
confidence: 78%
“…While this work was in progress, Shi et al . also found that miR-222 expression is increased in the USLs of women with POP compared to normal counterparts and that there is an inverse correlation between ERα protein and miR-222 expression 33 . In conclusion, based on Shi et al .…”
Section: Discussionmentioning
confidence: 78%
“…reported (49). A previous study indicated that miR-221 and miR-222, two regulatory factors of ESR1, negatively regulate the expression of ESR1 in patients with POP (50). The aforementioned results demonstrated that the ESR1 genotype may be a predisposing factor for POP and that it may be used as a potential therapeutic target for this disease.…”
Section: Genetic Susceptibility and Popmentioning
confidence: 77%
“…In the miRNA–hub gene network, 96 miRNAs were found to be associated with hub genes. Previous basic research has confirmed that among these miRNAs, miRNA-19, miRNA-30, miRNA-181, miRNA-138, and miRNA-221/222 could regulate the expression of critical genes supporting the pelvic floor, such as IGF-1, HOXA11, FBLN5, and estrogen receptor [ [54] , [55] , [56] , [57] ]. In the TF–hub gene network, TFs of CREM, GTF2A2, SUZ12, ZNF2, and ZNF512 in the network exhibited a high degree of interaction.…”
Section: Discussionmentioning
confidence: 99%